Lord jim - Conrad, Joseph (Globe Fearon West Nyack, N.Y., 1750)
"Lord Jim" is a novel by Joseph Conrad that follows the journey of a young, idealistic sailor, Jim, whose heroic aspirations are challenged by a moment of cowardice, leading to a life of redemption and self-discovery.